2023
DOI: 10.3390/brainsci13050815
|View full text |Cite
|
Sign up to set email alerts
|

Shared Mechanisms of GABAergic and Opioidergic Transmission Regulate Corticolimbic Reward Systems and Cognitive Aspects of Motivational Behaviors

Abstract: The functional interplay between the corticolimbic GABAergic and opioidergic systems plays a crucial role in regulating the reward system and cognitive aspects of motivational behaviors leading to the development of addictive behaviors and disorders. This review provides a summary of the shared mechanisms of GABAergic and opioidergic transmission, which modulate the activity of dopaminergic neurons located in the ventral tegmental area (VTA), the central hub of the reward mechanisms. This review comprehensivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 292 publications
0
5
0
Order By: Relevance
“…We also observe the specific elevation of glutamate neurotransmitters expression rate in losers’ hippocampus and dorsal striatum regions (orange circles) while GABAergic emission in Medium Spiny Neurons (MSN) of striatum was correspondingly lowered (blue circle). Notably, there is an observation that GABAergic neurons emission is modulated with opiodergic signaling, reported in a recent survey [ 14 ], in particular in VTA afferent.…”
Section: Resultsmentioning
confidence: 99%
“…We also observe the specific elevation of glutamate neurotransmitters expression rate in losers’ hippocampus and dorsal striatum regions (orange circles) while GABAergic emission in Medium Spiny Neurons (MSN) of striatum was correspondingly lowered (blue circle). Notably, there is an observation that GABAergic neurons emission is modulated with opiodergic signaling, reported in a recent survey [ 14 ], in particular in VTA afferent.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it has been demonstrated, through the use of opioid antagonists, that the antinociceptive effect of AEAP is partially mediated by opioid receptors [ 1 ]. Additionally, research has shown that the primary phytoconstituents present in AEAP roots are alkylamides [ 63 ], which are responsible for modulating opioidergic, serotoninergic, and GABAergic systems [ 61 ].The interaction between the opioid and GABAergic systems is crucial for understanding the rewarding and anxiolytic effects of opioids, as well as the processes involved in the development of opioid tolerance, dependence, and withdrawal [ 64 ]. We hypothesize that AEAP acts as a partial antagonist for opioids and GABAergic receptors, which could potentially explain the observed effects.…”
Section: Discussionmentioning
confidence: 99%
“…With this in mind, previous studies have demonstrated that the GABAergic system performs a pivotal function in opioid addiction. Moreover, studies have shown that positive modulators on the benzodiazepine site in the GABAA receptors (e.g., diazepam) and selective GABAA receptor agonists (e.g., muscimol) pacify morphine withdrawal signs (6,19,20,27).…”
Section: Discussionmentioning
confidence: 99%
“…Morphine dependence is associated with ailments such as anxiety, abdominal pain, diarrhea, etc. Earlier studies have shown that the continuous use of morphine affects the mesolimbic dopaminergic system in the ventral tegmental area (VTA) and leads to the development of tolerance and dependence (5,6). In this regard, studies have shown that several neural systems, such as the GABAergic and opioidergic systems, modulate the activity of the dopaminergic system, contributing to opioid tolerance and dependence (5,6).…”
Section: Introductionmentioning
confidence: 99%